DV or Not DV: That is the Question When Producing Video for the Internet - Gregory Gutenko (The Canadian Network for Innovation in Education (CNIE), 2002)
Pervasive advertising and marketing efforts promote consumer market digital video (DV) format camcorders as the ideal acquisition technology for Internet video production. A shared digital nature and simple interconnections between cameras and computers using IEEE1394/FireWire/i.Link® format digital cabling do suggest a natural affinity between DV and Internet production. However, experience with Web delivery reveals numerous obstacles associated with consumer-friendly camcorder design and feature sets that can severely compromise Internet streaming video quality. This paper describes the various features in consumer and industrial grade DV camcorder designs that lead to unnecessary image quality loss, and what must be done to avoid such loss. Conventional video production techniques that can lead to quality loss regardless of the camera technology used are also identified. A number of recommendations are offered that will help the videographer in an educational or production environment adapt to Internet limitations.